Fasilitasi Bimbingan Dan Pelatihan Kader Muda Imam Serta Khatib Kecamatan Sapuran & Kepil Kabupaten Wonosobo - Soffan Rizqi; Rahmat Lutfi Guefara; Robingun Suyud El Syam (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Friday sermons are a method of da'wah among Muslims which is always carried out in various places. The position of the preacher is very vital considering that it is related to the validity of worship. The aim of this service is to find out how to facilitate the guidance and training of young cadres of imams and preachers in Sapuran & Kepil District, Wonosobo Regency. The service stages go through three steps: coordination, implementation and evaluation. Qualitative research setting by collecting data through observation, interviews and documentation. The results of this activity show that facilitating guidance and training for young cadres of imams and preachers is very useful in that it can improve the quality of preachers and imams in carrying out Friday prayers. This contributes to understanding the importance of the content and strategy of the preacher in carrying out his duties, avoiding apathy which allows the congregation to become bored and not focus on listening to the sermon so that Friday prayers become dry of meaning. The conclusion specifies the essence that is meaningful for the reader, and how the research gaps are filled so that they contain elements of novelty and contribution to the wider area of da'wah.